A Short Review of All-Dielectric Topological Photonic Crystals - Wang, Hai-Xiao; Jiang, Jian-Hua (Frontiers in Physics, 2022)
Topological photonics is an emergent field at the cross of photonics and topological physics which opens our eyes to novel topological phenomena and versatile photonic effects. Photonic crystals (PhCs) are the optical analogs of conventional crystals that have proven to be an excellent photonic platform to explore topological physics. Here, we present a brief review of the all-dielectric topological PhCs by focusing on several prominent milestones of topological phases, such as the Su-Schrieffer–Heeger model, topological insulators, topological semimetals, and higher order topological phases. For each topological phase, the topological invariants and the intriguing topological properties as well as the potential applications are discussed. We conclude with the current challenge and the prospect of all-dielectric topological PhCs.